Correction: Transplantation of collagen sponge-based three-dimensional neural stem cells cultured in a RCCS facilitates locomotor functional recovery in spinal cord injury animals. (8th March 2022) - Zou, Yunlong; Yin, Yanyun; Xiao, Zhifeng; Zhao, Yannan; Han, Jin; Chen, Bing; Xu, Bai; Cui, Yi; Ma, Xu; Dai, Jianwu
Abstract : Correction for 'Transplantation of collagen sponge-based three-dimensional neural stem cells cultured in a RCCS facilitates locomotor functional recovery in spinal cord injury animals' by Yunlong Zou et al., Biomater. Sci., 2022, 10, 915–924. DOI: ; 10.1039/D1BM01744F .